Impact of Body Mass Index on Surgical and Oncological Outcomes in Laparoscopic Total Mesorectal Excision for Locally Advanced Rectal Cancer after Neoadjuvant 5-Fluorouracil-Based Chemoradiotherapy - Yanwu Sun; Pan Chi (Gastroenterology Research and Practice)
Aims. To evaluate the impact of body mass index (BMI) on the surgical outcome of laparoscopic total mesorectal excision (laTME) for locally advanced rectal cancer (LARC, clinically staged as UICC stage II/III) after neoadjuvant chemoradiotherapy (nCRT). Methods. 312 LARC patients undergoing laTME after nCRT were divided into nonobese (BMI < 25.0 kg/m2, n=249) and obese (BMI ≥ 25.0 kg/m2, n=63) groups. Preoperative radiotherapy was delivered in 45–50.4 Gy/25f, 5 days/week, and concurrent chemotherapy using FOLFOX or CapeOX. Technical feasibility, postoperative and oncological outcome were compared between groups. Results. Obese patients had significantly longer operative time (P=0.004). There was no significant difference regarding estimated blood loss, conversion, postoperative recovery, and morbidities. Multivariate analysis demonstrated that higher ASA score and abdominoperineal resection were risk factors for postoperative complications and diverting stoma was a protective factor. The length of resection margin, circumferential resection margin involvement, and number of lymph node retrieved were comparable. With a median follow-up time of 55 months (ranging 20–102 months), oncological outcome was comparable in terms of overall survival, local recurrence, and distant metastasis. Conclusions. Obesity does not affect surgical or oncological outcome of laTME after nCRT. LaTME may be feasible and safe to obese LARC patients after nCRT in a specialized center.